What can we learn about pension reform from Generational Accounts for the UK? - James Banks; Richard Disney; Zoë Oldfield (Institute for Fiscal Studies (IFS), 1999)
This paper considers the relevance of a set of generational accounts in informing policy debate in the UK. With regard to transparency, Generational Accounts can, under sensible assumptions, provide a useful summary statistic to supplement our analysis of government policy. Interpreting differences in the accounts across groups as measures of the incidence or redistributiveness of existing or proposed policies is more problematic. With respect to UK pension reform, within-cohort differences raise important issues. Finally we argue that past pension reforms have been characterised by inaccurate forecasts as opposed to a lack of understanding of the generational incidence of proposed policy.
Keywords: 330